Medical Embryology and its Importance in the 21st Century Curriculum: A mini review - Maani, Amr; Forma, Alicja; Baj, Jacek; Maciejewski, Ryszard (Italian Journal of Anatomy and Embryology, 2022)
Embryology is an essential tool in clinical practice especially for managing various medical disorders. As a course in medical schools, it is neither easy nor straightforward to understand and teach in the 21st century curriculum, as such, it is easy to overlook. As a discipline, embryology has entered a phase of unparalleled transition in its understanding base. This translates to a phase of abundant modification in the medical curriculum. A main critical issue of learning embryology is how extensively newer molecular medical embryology can be paired with the traditional approach to developmental of anatomy. Another issue would be which venue to be considered most effective in embryology instruction. The medical curriculum in during 21st century have different objectives, as well as different educational approach. As a consequence, this paper outlines a variety of aspects in which embryology could be presented as well as how it may be incorporated within the medical curriculum.